A conspiracy against Obamacare : the Volokh Conspiracy and the health care case - Barnett, Randy E.; Adler, Jonathan H.; Bernstein, David E.; Kerr, Orin S.; Kopel, David B.; Somin, Ilya.; Burrus, Trevor; SpringerLink (Online service) (New York : Imprint: Palgrave Macmillan, 2013)
The Affordable Care Act debate was one of the most important and most public examinations of the Constitution in our history. At the forefront of that debate were the bloggers of the Volokh Conspiracy who, from before the law was even passed, engaged in a spirited, erudite, and accessible discussion of the legal issues involved in the case.
Keywords: Science; Science; Science, general